Review Journal: Sustainable Fishery Supply Chain in Indonesia - Novi; BIMBI; Fitri Hardianti Wijaya; Andi Wirawan Risal (Universitas Cahaya Prima, 2026)
Indonesia, as the largest archipelago in the world, has a vast potential for fisheries resources, with a coastline stretching over 81,000 kilometers and waters rich in marine biodiversity. The fisheries sector plays a vital role in national food security and is also a source of income for millions of people relying on fishing, aquaculture, and fish processing activities. However, the sustainability of the fisheries sector faces serious challenges, including overexploitation, marine habitat degradation, and inefficiencies in the supply chain, leading to economic and environmental losses. This literature review aims to synthesize recent academic literature on sustainable fishery supply chains in Indonesia, focusing on regulatory and public policy aspects, quota-based resource management strategies, supply chain optimization in the downstream sector, and multi-stakeholder coordination through the Pentahelix model. The review shows that the integration of quota-based policies, the application of Sustainable Supply Chain Management (SSCM), and coordination among Pentahelix stakeholders are three key pillars that must be implemented simultaneously to achieve the sustainability of Indonesia's fisheries sector. This study is expected to provide practical recommendations for policymakers, academics, and practitioners in designing a fishery supply chain system that is not only economically efficient but also socially equitable and environmentally sustainable.